Reframing Development with Living Infrastructure: A Case Study of the South Essex Green and Blue Infrastructure (SEGBI) Strategy - Alexandra Steed (Proceedings of the International Conference of Contemporary Affairs in Architecture and Urbanism-ICCAUA)
We are headed towards a global crisis: climate change, ecological collapse, and population expansion are threatening planetary boundaries as never before. We must urgently tackle these issues together. Entire ecosystems must be regenerated rather than trying to tackle issues in isolation. We were tasked with creating a green and blue infrastructure strategy in the 70,000-hectare region of South Essex - a place threatened with sea-level rise, flooding, and significant growth pressures. A ‘land-based’ methodology was applied, and a co-design approach was undertaken with community stakeholders to create a spatial framework based on living biophysical systems and ecological infrastructures that can reshape and drive future planning and development. The resulting SEGBI Study provided a ground-breaking model for the delivery of sustainable growth. It demonstrated how the application of living infrastructure has the capacity to address climate change and ecological collapse while also supporting sustainable housing, resilient communities, and regenerative infrastructures.